2021
DOI: 10.21203/rs.3.rs-280764/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Improving Antibacterial and Anti-biofilmic properties of urological catheters with Eucalyptus, Rosemary, Green tea and Ziziphora extracts by impregnation method

Abstract: The main complications of urinary catheters are the bacteria's biofilm formation and the urinary tract infection caused by gram-positive and gram-negative bacteria. In the recent years, the attention has changed its direction toward the antimicrobial, anti-biofilmic, and hydrophobicity effects of herbal extracts. Some of these extracts can inhibit the colonization of the two bacteria Staphylococcus aureus and Escherichia coli which are resistant to antibiotics. These bacteria can stick to the surface of polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…Previous research concluded that the use of natural products in urinary catheters significantly reduced colonization (Jordan et al 2015) and bacterial adhesion (Adesina et al 2015), showing an antibiofilm effect (Cai et al 2014;Namasivayam & Roy 2013;Akhlaghi-Ardekani et al 2021), with more promising results than standard antibiotics (Ezeonu et al 2009).…”
Section: Potential Of Endophytics and Compoundsmentioning
confidence: 99%
“…Previous research concluded that the use of natural products in urinary catheters significantly reduced colonization (Jordan et al 2015) and bacterial adhesion (Adesina et al 2015), showing an antibiofilm effect (Cai et al 2014;Namasivayam & Roy 2013;Akhlaghi-Ardekani et al 2021), with more promising results than standard antibiotics (Ezeonu et al 2009).…”
Section: Potential Of Endophytics and Compoundsmentioning
confidence: 99%
“…Many plant extracts have been used to endow surface antibacterial characteristics to catheters. Aqueous extracts of Aloe vera, Carica papaya, Psidium guajava, Gongronema latifolium, Ocimum gratissimum, Vernonia amygdalina [15], Evolvulus alsinoides [16], and Ziziphora [17,18], ethanolic extracts of Azadirachta indica [19], Camellia sinensis, Eucalyptus, and Salvia rosmarinus [17,18], and methanolic extracts of Mangifera indica, Ocimum gratissimum, and Psidium guajava [20,21], among others, have been used to prevent catheter colonization from clinically relevant bacteria such as Escherichia coli, Klebsiella pneumoniae, Proteus mirabilis, Pseudomonas spp., Staphylococcus spp., and urine bacteria. However, although biocompatibility plays an essential role in the clinical applications of materials, the hemolytic activity of extract-coated catheters has not been reported yet [12].…”
Section: Introductionmentioning
confidence: 99%